Gene expression deficits in pontine locus coeruleus astrocytes in men with major depressive disorder - Chandley, Michelle J.; Szebeni, Katalin; Szebeni, Attila; Crawford, Jessica; Ordway, Gregory A.; Stockmeier, Craig A.; Miguel-Hidalgo, Jose Javier; Turecki, Gustavo (Journal of psychiatry & neuroscience, 2013)
Norepinephrine and glutamate are among several neurotransmitters implicated in the neuropathology of major depressive disorder (MDD). Glia deficits have also been demonstrated in people with MDD, and glia are critical modulators of central glutamatergic transmission. We studied glia in men with MDD in the region of the brain (locus coeruleus; LC) where noradrenergic neuronal cell bodies reside and receive glutamatergic input. The expression of 3 glutamate-related genes (SLC1A3, SLC1A2, GLUL) concentrated in glia and a glia gene (GFAP) were measured in postmortem tissues from men with MDD and from paired psychiatrically healthy controls. Initial gene expression analysis of RNA isolated from homogenized tissue (n = 9–10 pairs) containing the LC were followed by detailed analysis of gene expressions in astrocytes and oligodendrocytes (n = 6–7 pairs) laser captured from the LC region. We assessed protein changes in GFAP using immunohistochemistry and immunoblotting (n = 7–14 pairs). Astrocytes, but not oligodendrocytes, demonstrated robust reductions in the expression of SLC1A3 and SLC1A2, whereas GLUL expression was unchanged. GFAP expression was lower in astrocytes, and we confirmed reduced GFAP protein in the LC using immunostaining methods. Reduced expression of protein products of SLC1A3 and SLC1A2 could not be confirmed because of insufficient amounts of LC tissue for these assays. Whether gene expression abnormalities were associated with only MDD and not with suicide could not be confirmed because most of the decedents who had MDD died by suicide. Major depressive disorder is associated with unhealthy astrocytes in the noradrenergic LC, characterized here by a reduction in astrocyte glutamate transporter expression. These findings suggest that increased glutamatergic activity in the LC occurs in men with MDD.